Trends in surgical management of spinal metastases in a Singaporean tertiary referral center: a 17-year retrospective review - Tan, Jiong Hao Jonathan; Hallinan, James Thomas Patrick Decourcy; Lee, Renick; Chan, Yiong Huak; Tan, Tuan Hao; Ang, Shi Wei; Tan, Le Tian Isaac; Tan, Joelle Hwee Inn; Sin, Qinxiang Shant; Hey, Dennis Hwee Weng; Lau, Leok Lim; Thambiah, Joseph; et al. (Frontiers in Oncology, 2023)
Introduction: Surgical treatment is increasingly the treatment of choice in cancer patients with epidural spinal cord compression and spinal instability. There has also been an evolution in surgical treatment with the advent of minimally invasive surgical (MIS) techniques and separation surgery. This paper aims to investigate the changes in epidemiology, surgical technique, outcomes and complications in the last 17 years in a tertiary referral center in Singapore.Methods: This is a retrospective study of 383 patients with surgically treated spinal metastases treated